Standardising Homoeopathic Products: Challenges, Benefits, and Global Trends (Homoeopathy for All, 2025)
1. What has led to the recent push for the standardization of homoeopathic products and services? As more individuals are turning to Traditional Healthcare Systems, ensuring consistent quality, safety, and efficacy in Ayush products and services has become essential. Standardisation in Homoeopathy is of crucial importance in the present times. Standards create a structure that improves efficiency in processes, helps spread new technologies, and makes it easier to achieve cost savings. Secondly, they increase consumer protection and trust, making it easier for products to enter the market. Further, they can promote trade by lowering technical barriers. Finally, standards support public policies and offer alternatives that align with regulations.
Keywords: technologies; protection; individuals